PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BANK BPR SINDANG BINA HARTA LUBUK LINGGAU - Herman Efrizal (JURNAL KOMPETITIF, 2015)
ABSTRACTThis research studies the correlation among Leadership,Ã‚Â  Communication andÃ‚Â  Motivation with officer Perfomance at Govermance.Bank BPR Sindang Bina Harta Lubuk Linggau . This Research was done during 4 ( six) months included design, executing and report the result.The research of this case study aims to know the correlation amongÃ‚Â  Leadership Comunication and Motivation with officer Perfomance at Govermance.Bank BPR Sindang Bina Harta Lubuk Linggau either through parsial and also together. The population In this research are the officer at Govermance. Bank BPR Sindang Bina Harta Lubuk Linggau , totally 34 people.Keywords : Communication, Leadership and Motivation Officer Performance.Ã‚Â